PROTOCOL: Mindfulness‐based interventions for improving tic‐related symptoms in children and adults with chronic tic disorder and Tourette's disorder: A systematic review - Ilana Singer; Méliza Gagnon; Julie B. Leclerc (Campbell Systematic Reviews)
Abstract This is a protocol for a Cochrane Review (prototype). The objectives are as follows: This systematic review aims to summarize the available scientific literature on the effect of mindfulness‐based approaches in children and adults with Chronic Tic Disorder (CTD) or Tourette Disorder (TD). More specifically, the research question is: What is the effectiveness of mindfulness‐based interventions in reducing tic severity and improving overall functioning, quality of life, and co‐occurring symptoms in children and adults with CTD or TD?